Evaluating the Environmental Quality of Forest Remnants Using Landscape Metrics - Longo, Regina Márcia; da Silva, Alessandra Leite; Ribeiro, Admilson Irio [UNESP]; Gomes, Raissa Caroline; Sperandio, Fabricio Camillo; Nunes, Adélia N. (MDPI, 2024)
Forest remnants are hotspots of biodiversity and play an important role in providing services such as regulating the climate, reducing surface runoff, helping erosion control, protecting and contributing to the balance of ecosystems, and other functions. Despite this, natural vegetation is fragmented and limited to a few remnants, which are gradually suffering from anthropogenic pressures. Assessing the environmental quality of these remnants is therefore vital to understanding their current condition and to provide support for their conservation. This study aims to assess the environmental quality of forest remnants in six water basins in the municipality of Campinas/SP, Brazil. Forest remnants were mapped, and their environmental quality was assessed by applying an analytic hierarchy process (AHP), considering a set of structural landscape metrics previously selected from the literature. Of the 2319 forest remnants evaluated, 4.5% and 30%, respectively, registered high and low environmental quality. The Atibaia and Jaguari basins recorded the highest number of environmentally fragile remnants due to their small size and being predominantly elongated, and to the high erodibility of the soil. In the Anhumas, Capivari, Capivari-Mirim, and Quilombo basins, medium-sized forest remnants predominate. There is a greater distance between them, with a high intensity of land use/land cover in their surroundings, related to the prevalence of urbanized areas. Specific management actions should be taken in each of these basins.
Keywords: environmental quality; forest remnants; landscape metrics; river basins